PERJUDIAN ONLINE DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Christianata, Christianata (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2014)
Freedome of expression and creativitiy in society are some of period advancement`sconsequences. Those occur both in real world and virtual world. Along with the advances in digitaltechnology, there are no boundaries and barriers in making transactions. However , it has to beremembered that various type of crimes happened in digital world. One if them is online gambling. Therise of online gambling has come to the noticeable point the government and society have to standtogether eradicate online gambling. Legal instruments also needed to penalixe online gamblers